Die onderrigleier se rol ten opsigte van vraagstukke rondom religie en etiek binne skoolverband - Rhodes, B. D.(Bernard David) (Stellenbosch : Stellenbosch University, 2012)
Tesis (M. Ed.) -- Universiteit van Stellenbosch, 1997.